New genome sequences of Gamboa Viruses (Family Bunyaviridae, Genus Orthobunyavirus) isolated in Panama and Argentina - Nunes, M?rcio Roberto Teixeira (American Society for Microbiology, 2016)
We describe here the nearly complete open reading frame (ORF) of five Gamboa virus strains isolated in Panama and Argentina. The viruses with complete ORF showed the regular genome organization observed in other orthobunyaviruses with exception to the presence of NSs protein. All predicted proteins showed homology with viruses belonging to members of the family Bunyaviridae.